An effective approach to the treatment of chronic recurrent genital herpes: An open-label, cohort, prospective study - Oksana A. Gizinger; Akim R. Gaziev; Sergey V. Stovbun (Гинекология)
Background. Herpes virus infection poses a serious medical and social danger both at the country and global levels, inducing severe disorders leading to pregnancy complications, reproductive losses, and proliferative diseases.